THE IMPACT OF BRAND IMAGE AND CONSUMERS TRUST ON PURCHASE DECISION AT STARBUCKS COFFEE PONTIANAK - Tri Djoko Sulistio; Rina Fitriana (Sean Institute, 2022)
This study was conducted with the aim of knowing the effect of Brand Image (X1) and Consumer Trust (X2) on Purchase Decisions (Y) at Starbucks Coffee Pontianak. The method used in this study is quantitative using a sample of 90 respondents who were measured using a questionnaire consisting of 24 statements. The tests carried out in this study were validity tests, reliability tests, correlation coefficient tests, simple linear analysis, multiple linear analysis, correlation tests and hypothesis testing. Based on the research that has been done, namely Brand Image at Starbucks Coffee Pontianak with a mean of 3.05 in the good category, Consumer Trust at Starbucks Coffee Pontianak with a mean of 3.26 in the very good category and Purchase Decisions at Starbucks Coffee Pontianak with a mean of 2.95 in the good category. Brand Image and Consumer Beliefs have a strong relationship with Purchase Decisions. Brand Image (X1) and Consumer Trust (X2) have an influence on Purchase Decision (Y) by 71.6% and the remaining 28.4% is influenced by other factors not examined in this study.